A Delphi consensus study to determine the workload components and activity standards of dietitians in South Africa’s central and tertiary public hospitals - Vertharani Nolene Naicker; Keshan Naidoo; Jane W. Muchiri; Modiehi Heather Legodi (Human Resources for Health, 2024)
Abstract Background The global Human Resources for Health (HRH) strategy emphasizes the need to invest in HRH to meet population needs and improve the provision of quality health care services. In South Africa, dietitians are recognized as registered professionals who provide nutrition services. In this paper, we used 2 key steps (3 and 4) of the eight step World Health Organization (WHO) Workload Indicators of Staffing Need (WISN) methodology to determine the workload components and activity standards for dietitians at South African central and tertiary public hospitals. Methods All (9) provincial nutrition managers (phase one) and 21 out of a total 22 head dietitians at central and tertiary public hospitals (phase two) participated in an online survey. In phase one, the provincial managers provided the job descriptions (JDs) of dietitians in their provinces, and the JDs were analyzed to determine the baseline workload components. In phase two, dietitians participated in a multi-stage Delphi process to reach consensus on workload components and activity standards. Consensus was deemed to be agreement of 70% or more, while the median of participants’ responses was used to obtain consensus on the activity standards. Results The JDs of dietitians were a useful baseline for the consensus exercise as there were no other suitable source documents. The response rate was 100% for all three rounds of the Delphi survey. Dietitians reached agreement (consensus ≥ 70%) on 92% of proposed workload components and activity standards. Following the removal of duplicate and certain administrative activities, a total of 15 health, 15 support and 15 additional service activities with aligned activity standards resulted from the consensus exercise. Conclusion The Delphi technique was a suitable method for reaching agreement on workload components and activity standards for dietitians at South African central and tertiary public hospitals. The findings from this study can now be used to compile a standardized list of workload components and activity standards and ultimately to determine dietetic staffing needs for the central and tertiary public hospital level of care.